Rhinoplasty Results Are Influenced by Non-nasal Features - Wang, Frederick; Xu, Ginger; Gruber, Ronald Peter (Facial Plastic Surgery, 2017)
Rhinoplasty results are evaluated both objectively and subjectively following any procedure by plastic surgeons and nonplastic surgeons at meetings, in publications, and online. We aim to evaluate whether subjective aesthetics of non-nasal features, such as the eyes and lips, would influence the overall evaluation of rhinoplasty results. We matched pairs of photographs of patients who had undergone aesthetic rhinoplasty by sex, age, and skin tone. We transferred the eyes/eyebrows and lips from the photographs of the donor patient onto the photographs of the original patient to create composite photographs. Plastic surgeons were asked to rate the rhinoplasty results objectively, and non-plastic surgeons were asked to rate the overall attractiveness of 16 sets of photographs (8 originals and 8 composites). Postoperative photographs that were deemed to be more attractive were associated with higher ratings of rhinoplasty improvement. The objective nasal result may be influenced by non-nasal aesthetic factors as rhinoplasty surgeons gave higher ratings to more attractive faces. Greater emphasis on neutralizing non-nasal factors in pre- and postoperative photographs should be considered.
Keywords: rhinoplasty; non-nasal; aesthetic evaluation